Wage inequality in the Netherlands: Evidence, trends, and explanations - Hamouda, Omar F.; Groot, Henri L.F. de; Groot, Stefan P.T. (Journal of Income Distribution®, 2014)
For many years, the Netherlands has been considered an exception to the growing trend of wage inequality.